John dies at the end - Pargin, Jason, 1975- (Pargin, Jason, 1975- John dies at the end (Series), 2013)
This may be the story of John and David, a drug called soy sauce, and other-worldly beings invading the planet. Or, it may be the story of two beer-drinking friends who live in an unnamed Midwestern town and only think something horrific is going on. But the important thing is, according to the narrator, "None of this is my fault."